Synergistic effects of amorphous porous materials and anhydrous Na2CO3 on the performance of bricks with high municipal sewage sludge content. (20th January 2021) - Yang, Fengming; Zhou, Wentao; Zhu, Ruijian; Dai, Ge; Wang, Weijie; Wang, Wenlong; Guo, Xinli; Jiang, Jinyang; Wang, Zengmei
Abstract: The shortage of land resources around the world has led to the increasing pressure of clay brick production in recent years. On the other side, as a by-product of the sewage treatment, the mineral crystalline phase and chemical composition of municipal sewage sludge (MSS) are similar to those of clay, which also need to be treated urgently. Owing to the porous structure originating from large amounts of organics evaporation at elevated temperature in MSS, it can be utilized as the thermal insulation bricks. However, the component complexity of MSS will result in the decrease of strength and durability of bricks, thus the replacement amount of MSS was generally less than 30%. To achieve optimal experimental conditions for thermal insulation bricks with large amounts of MSS, up to 40% dried MSS, amorphous rice husk ash (RHA) and anhydrous Na2 CO3 (ANC) as the raw materials in this work, the dosage and temperature were set as variable parameters. The results showed that 0.178 W/(mK) of thermal conductivity of bricks with 9.6 MPa of compressive strength, and 1336.2 kg/m 3 of bulk density were obtained under the optimal conditions: 4: 5: 1 of the weight ratio of MSS: Clay: RHA, 3% of additional dose of ANC, 1075 °C of sintering temperature. The obtained bricks revealed excellent durability and sorption properties for heavy metals through the freeze-thaw cycle test and leachability test. Overall results manifested one effective approach for solid waste treatment through cleaner production and paved one way for sustainable, economical and energy-saving construction.